Crime scene investigation and reconstruction - Ogle, Robert R.; Plotkin, Sharon L. (Pearson, 2018)
Using a systematic approach, Crime Scene Investigation and Reconstruction, Fourth Edition, outlines techniques that help investigators answer the critical what, who, and when questions of crime scene investigations. With a focus on crime scene processing, the book includes the latest on database technologies, digital cameras, DNA analyses, and computer-aided crime scene reconstructions. Each chapter includes introductions and summaries that demystify the technical aspects of the field. This edition features a new coauthor with almost 20 years of experience handling crime scene work; ready-to-use forms to help with proper documentation of crime scenes and collection of evidence; and updated content, including new photographic techniques, coverage of detection and enhancement of evidence on crime scenes, and a new chapter on entomology.